Increased Autoimmunity in Individuals With Down Syndrome and Moyamoya Disease - Santoro, Jonathan D.; Lee, Sarah; Wang, Anthony C.; Ho, Eugenia; Nagesh, Deepti; Khoshnood, Mellad; Tanna, Runi; Durazo-Arvizu, Ramon A.; Manning, Melanie A.; Skotko, Brian G.; Steinberg, Gary K.; Rafii, Michael S. (Frontiers in Neurology, 2021)
Objective: To determine if elevated rates of autoimmune disease are present in children with both Down syndrome and moyamoya disease given the high rates of autoimmune disease reported in both conditions and unknown etiology of angiopathy in this population. Methods: A multi-center retrospective case-control study of children with Down syndrome and moyamoya syndrome, idiopathic moyamoya disease, and Down syndrome without cerebrovascular disease was performed. Outcome measures included presence of autoimmune disease, presence of autoantibodies and angiopathy severity data. Comparisons across groups was performed using the Kruskal-Wallis, χ2 and multivariate Poisson regression. Results: The prevalence of autoimmune disease were 57.7, 20.3, and 35.3% in persons with Down syndrome and moyamoya syndrome, idiopathic moyamoya disease, and Down syndrome only groups, respectively (p < 0.001). The prevalence of autoimmune disease among children with Down syndrome and moyamoya syndrome is 3.2 times (p < 0.001, 95% CI: 1.82–5.58) higher than the idiopathic moyamoya group and 1.5 times (p = 0.002, 95% CI: 1.17–1.99) higher than the Down syndrome only group when adjusting for age and sex. The most common autoimmune diseases were thyroid disorders, type I diabetes and Celiac disease. No individuals with idiopathic moyamoya disease had more than one type of autoimmune disorder while 15.4% of individuals with Down syndrome and moyamoya syndrome and 4.8% of individuals with Down syndrome only had >1 disorder (p = 0.05, 95%CI: 1.08–6.08). Interpretation: This study reports elevated rates of autoimmune disease in persons with Down syndrome and moyamoya syndrome providing a nidus for study of the role of autoimmunity in angiopathy in this population.